#### Answer

Difference between the sum of first 14 terms of $b_{n}$ and the Sum of first 14 terms of $a_{n}$ = 497 - (-350) = 497 +350 = 847

#### Work Step by Step

From graph First term $a_{1}$ = 1
Second term $a_{2}$ = -3
Third term $a_{3}$ = -7
Common difference (d) = -7 + 3 = -3 - 1 = -4
$14^{th}$ term $a_{14}$ = 1 + (14 - 1)(-4) = 1 - 52 = -51
Sequence = 1, -3, -7, . . . . . -51
Sum of first 14 terms of $a_{n}$ = $\frac{14}{2}$(1 - 51) = 7$\times$(-50) = -350
From graph
First term $b_{1}$ = 3
Second term $b_{2}$ = 8
Third term $b_{3}$ = 13
Common difference (d) = 13 - 8 = 8 - 3 = 5
$14^{th}$ term $b_{14}$ = 3 + (14-1)5 = 3 + 65 = 68
Sequence = 3, 8, 13, . . . . . 68
Sum of first 14 terms of $b_{n}$ = $\frac{14}{2}$(3 + 68) = 7$\times$71 = 497
Difference between the sum of first 14 terms of $b_{n}$ and the Sum of first 14 terms of $a_{n}$ = 497 - (-350) = 497 +350 = 847